Curved magnesium aluminate spinel transparent fairing and preparation method thereof
By using high-temperature resistant mold molds and thermal isostatic pressing technology, the curved magnesium-aluminum spinel transparent fairing directly heat-pressed to form a curved magnesium-aluminum spinel transparent fairing in the prior art solves the problems of complex preparation process, high cost and easy product cracking, achieving uniform and excellent material performance and reduction of preparation cost.
Patent Information
- Application Number
- CN202411977059.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-11
AI Technical Summary
In the prior art, the preparation process of curved magnesium-aluminum spinel transparent fairing is complex, the cost is high, and the product is prone to cracking and deformation.
The sample is shaped by high-temperature resistant curved molds. Through direct hot pressing molding, the powder is formed into a curved magnesium-aluminum spinel transparent fairing with a curved surface and a curved surface, and is sintered by thermal isostatic pressing technology.
It achieves uniform and excellent material performance, reduces preparation cost and process complexity, avoids the problems of sample cracking and mold compression fracture, and improves the transparency and mechanical properties of the fairing.
Smart Images

Figure CN119797905A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic material preparation, and in particular to a curved magnesium-aluminum spinel transparent fairing and a preparation method thereof. Background Art
[0002] As a key component of the infrared optoelectronic imaging guidance system structure, the fairing can effectively reduce the aerodynamic and thermal coupling effect of high-speed aircraft, achieve the purpose of reducing aerodynamic drag, obtaining better stealth capability and target field of view, and is an important choice and development direction for future weapons and equipment optical precision guidance systems. Magnesium aluminum spinel (MgAl2O4) has isotropy and its advantages include high light transmittance, wide transparent band, high temperature resistance, wear resistance, corrosion resistance, impact resistance, high strength, high hardness, easy processing, and low cost. It is one of the ideal candidate materials for the preparation of missile fairings. It can not only fully meet the optical and mechanical performance requirements of high Mach missile fairings, but also has the advantage of high cost performance.
[0003] At present, the traditional preparation method of curved magnesium aluminum spinel transparent fairing is to obtain a blank by dry pressing of powder, and then obtain it through degumming, hot pressing sintering, polishing and hot isostatic pressing sintering. The preparation process is cumbersome and the cycle is long. In addition, when the curved spinel transparent fairing is prepared by the traditional hot pressing method, the ceramic blank is subjected to uneven forces in all directions of the curved surface during the hot pressing sintering process, and the thermal shrinkage rates in different directions are also different. It is easy to cause uneven material due to uneven pressure, resulting in uneven internal stress of the material, which makes the sample prone to cracks or even direct cracking. More importantly, due to the large difference in thermal shrinkage rates at different positions of the curved sample during the hot pressing process, the sample is easy to deform, resulting in the problem that the fairing hot pressing mold and the sample cannot be fully adapted during the sintering process, which can easily cause the hot pressing mold to rupture under pressure and increase costs.
[0004] Based on this, the development of a curved magnesium-aluminum spinel transparent fairing with low cost, simple route and uniform and excellent material properties is of great significance for the research of ceramic materials. Summary of the invention
[0005] In view of the problems in the prior art that the preparation process of the curved magnesium-aluminum spinel transparent fairing is complicated, the cost is high, and the product is prone to cracking and deformation, the present invention provides a curved magnesium-aluminum spinel transparent fairing and a preparation method thereof. To achieve the above-mentioned invention purpose, the present invention provides the following technical solutions:
[0006] The first aspect of the present invention provides a method for preparing a curved magnesium-aluminum spinel transparent fairing, comprising the following steps: Step 1: Evenly mix the magnesium aluminum spinel powder, sintering aid and deionized water, ball mill, dry and sieve to obtain modified powder; Step 2: adding part of the modified powder into a hot pressing mold, placing a high temperature resistant curved mold above the modified powder, with the concave surface of the high temperature resistant curved mold facing upward and the convex surface embedded in the modified powder, and adding the remaining modified powder to fill the concave surface of the high temperature resistant curved mold to obtain a sintered precursor; Step 3, heating the sintered precursor to 750°C-850°C once, and keeping it warm once to obtain a pre-treated sintered product; heating the pre-treated sintered product to 1140°C-1160°C for a second time under an inert atmosphere, and keeping it warm for a second time to obtain a secondary sintered product; heating the secondary sintered product to 1500°C-1600°C for a third time under a pressure of 30MPa-40MPa, and keeping it warm for a third time to obtain a hot pressed sample; Step 4, separating the hot pressed sample from the mold, processing and polishing, and obtaining a rough fairing product; Step 5: In an inert atmosphere at 150MPa-170MPa, the temperature of the raw fairing is raised to 1650°C. -1750℃, sintering is carried out to obtain a curved magnesium-aluminum spinel transparent fairing.
[0007] The present invention uses powder as raw material, utilizes a high temperature resistant curved mold to shape the sample, and uses a direct hot pressing method to form the powder into a curved magnesium aluminum spinel transparent fairing that is cylindrical as a whole and has a curved bottom. The present invention utilizes a semicircular or bowl-shaped high temperature resistant curved mold to shape the sample so that the modified powder is subjected to uniform force during the hot pressing process, thereby avoiding the problem of sample cracking caused by uneven pressure during the hot pressing process, and at the same time avoiding the problem of sample deformation caused by compression due to the incompatibility between the mold and the sample. In addition, direct hot pressing of the powder can eliminate the early ceramic blank forming process and the degumming process of the ceramic blank, thereby reducing the overall process flow, shortening the preparation cycle, and reducing the preparation cost, providing a new preparation idea for the curved magnesium aluminum spinel transparent fairing. At the same time, the present invention can promote the densification of the fairing, reduce pores and grain boundary scattering, and improve transparency and mechanical properties through hot pressing and sintering treatment. During the hot pressing and sintering process, since heating and pressurization are carried out simultaneously, the powder is in a thermoplastic state, which is conducive to the contact diffusion and mass transfer process of the particles, thereby promoting the densification of the green body, reducing the sintering temperature and shortening the sintering time, helping to resist grain growth, and reducing the porosity in the sintered body, thereby obtaining a sintered body with higher density and better mechanical properties.
[0008] At the same time, staged heating can control the reaction rate of raw materials at different temperatures, avoid structural defects or uneven reactions caused by too fast temperature changes, reduce thermal stress caused by rapid temperature changes, and avoid cracking or damage of ceramic materials. In different temperature ranges, magnesium-aluminum spinel undergoes different phase transitions, which can ensure that these transitions are carried out at appropriate temperatures, thereby obtaining ideal phase structures and microstructures. Defective spinel crystals will appear at low temperatures, and then crystallize into pure spinel phases at 750℃-850℃. As the temperature continues to rise, the powder begins to densify and the pores decrease. As pressure is applied, magnesium-aluminum spinel powder continues to densify. In this process, particle crushing, rearrangement and dislocation mechanisms work together to promote the densification of the material. In the final stage of the hot pressing process, by controlling the sintering temperature and time, transparent spinel ceramics with high density and fine grain size are obtained.
[0009] In addition, the hot isostatic pressing technology used in the present invention can significantly improve the density of ceramics, refine the grain size, reduce or eliminate internal residual pores and micro-defects, and significantly improve the optical quality and mechanical strength of ceramics by sintering ceramics under high temperature and high pressure.
[0010] Preferably, the sintering aid in step one is lithium fluoride.
[0011] The present invention can effectively improve the sintering degree and mechanical properties of magnesia-alumina spinel powder by limiting the sintering aid to lithium fluoride.
[0012] Preferably, the purity of the magnesia-alumina spinel powder in step 1 is ≥ 99.9%.
[0013] The present invention can effectively improve the comprehensive performance of the finally formed curved magnesium-aluminum spinel transparent fairing by limiting the purity of the magnesium-aluminum spinel powder.
[0014] Preferably, the amount of the sintering aid added in step 1 is 1wt%-1.5wt% of the magnesia-alumina spinel powder.
[0015] The present invention can avoid the poor performance of the curved magnesia-aluminum spinel fairing caused by adding too much sintering aid by limiting the added amount of sintering aid, and can also avoid the poor sintering effect of the curved magnesia-aluminum spinel fairing caused by adding too little sintering aid.
[0016] Preferably, in step one, the mass volume ratio of the magnesium aluminum spinel powder to the deionized water is 1g:(3mL-4mL).
[0017] The present invention can effectively ensure the solid content of the slurry by limiting the mass volume ratio of the magnesia-alumina spinel powder and the deionized water.
[0018] Preferably, the rotation speed of the ball mill in step 1 is 50 rpm-60 rpm; and the time of the ball mill is 24 h-26 h.
[0019] The present invention can effectively ensure the slurry particle size and specific surface area by limiting the rotation speed and time of ball milling, and further improve the densification and transparency of the curved magnesium aluminum spinel fairing.
[0020] Preferably, the mesh size of the sieving in step 1 is 10-80 mesh.
[0021] The present invention can effectively ensure the particle size and uniformity of the magnesia-alumina spinel powder by limiting the mesh number of the sieve, and further improve the densification and transparency of the curved magnesia-alumina spinel fairing.
[0022] Preferably, in step 2, the portion of the modified powder is 60%-80% of the total volume of the modified powder.
[0023] The present invention can ensure the final performance of the finally prepared curved magnesia-alumina spinel fairing by limiting the content of the modified powder.
[0024] Preferably, in step 2, the high temperature resistant curved mold is curved molybdenum paper.
[0025] The present invention limits the material of the high-temperature resistant curved mold to molybdenum, thereby avoiding the introduction of other impurities in the process of preparing the curved magnesium-aluminum spinel transparent fairing.
[0026] Preferably, in step three, the first heating, the second heating and the third heating are all heated by programmed heating; wherein the heating rate of the first heating is 4°C / min-6°C / min; the heating rates of the second heating and the third heating are both 3°C / min-4°C / min.
[0027] Preferably, in step 3, the time of the first insulation is 60 min-90 min; and / or
[0028] Preferably, in step 3, the secondary insulation time is 9 min-12 min; and / or
[0029] Preferably, in step three, the three insulation times are 4h-6h.
[0030] The present invention can further avoid structural defects or uneven reactions caused by too rapid temperature changes by limiting specific parameters of programmed temperature rise, reduce thermal stress caused by rapid temperature changes, and avoid cracking or breakage of ceramic materials.
[0031] Preferably, in step five, the sintering holding time is 2h-4h.
[0032] Preferably, in step five, the heating rate of the fairing crude product to 1650°C-1750°C is 3°C / min-7°C / min.
[0033] The present invention can promote the densification of the fairing, reduce pores and grain boundary scattering, and improve transparency and mechanical properties by limiting the sintering heating rate and the heat preservation time.
[0034] The second aspect of the present invention provides a curved magnesium-aluminum spinel transparent fairing, which is prepared by using the preparation method of the curved magnesium-aluminum spinel transparent fairing.
[0035] The third aspect of the present invention provides an application of the curved magnesium aluminum spinel transparent fairing in an infrared optoelectronic imaging guidance system.
[0035] In summary, the present invention includes at least one of the following beneficial technical effects: 1. The present invention uses a high-temperature resistant curved mold to shape the sample so that the modified powder can be subjected to uniform force during the hot pressing process, thereby avoiding the problem of sample cracking caused by uneven pressure during the hot pressing process, and at the same time avoiding the problem of sample deformation caused by compressive deformation due to the incompatibility between the mold and the sample. In addition, the direct hot pressing of the powder can save the early ceramic blank forming process and the degumming process of the ceramic blank, reduce the overall process flow, shorten the preparation cycle, and reduce the preparation cost, providing a new preparation idea for the curved magnesium aluminum spinel transparent fairing; 2. The present invention can promote the densification of the fairing, reduce pores and grain boundary scattering, and improve transparency and mechanical properties through hot pressing sintering treatment. During the hot pressing sintering process, since heating and pressurization are carried out simultaneously, the powder is in a thermoplastic state, which is conducive to the contact diffusion and mass transfer process of the particles, thereby promoting the densification of the blank, reducing the sintering temperature and shortening the sintering time, helping to resist grain growth, and reducing the porosity in the sintered body, thereby obtaining a sintered body with higher density and better mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is a cross-sectional view of a hot pressing mold containing modified powders of the present invention;
[0037] Figure 2 This is the process flow of hot pressing sample processing of the present invention;
[0038] Explanation of the accompanying reference numerals: 1. graphite gasket; 2. modified powder; 3. high temperature resistant curved mold; 4. graphite sleeve. DETAILED DESCRIPTION
[0039] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0040] Example 1
[0041] A method for preparing a curved magnesium-aluminum spinel transparent fairing comprises the following steps: Step 1: Mix 99.93% pure magnesium aluminum spinel powder, 3.233 g lithium fluoride and 1120 mL deionized water, ball mill at a speed of 50 rpm for 24 h, dry at a temperature of 105 ° C for 28 h, and pass through a 40-mesh sieve to obtain a modified powder; Step 2, adding 70wt% of the modified powder into a hot pressing mold, placing a curved molybdenum paper above the modified powder, so that the concave surface of the curved molybdenum paper faces upward and the convex surface is embedded in the modified powder, and adding the remaining modified powder to fill the concave surface of the curved molybdenum paper to obtain a sintered precursor; Step 3, heating the sintered precursor to 800°C at a heating rate of 5°C / min, and keeping it warm for 60 minutes to obtain a pretreated sintered product; in an inert atmosphere, heating the pretreated sintered product to 1150°C at a heating rate of 4°C / min for a second time, and keeping it warm for 10 minutes to obtain a secondary sintered product; under a pressure of 35MPa, heating the secondary sintered product to 1550°C at a heating rate of 4°C / min for three times, keeping it warm for 5 hours for three times, naturally cooling to 1500°C, releasing the pressure, and naturally cooling to room temperature to obtain a hot pressed sample; Step 4: Take the hot-pressed sample out of the hot-pressing mold, separate the sample along the molybdenum paper, and the lower half is the curved surface sample blank, which is processed and polished according to size requirements to obtain a rough fairing; Step 5: In an inert atmosphere and at 160 MPa, the crude fairing product is heated to 1650° C. for sintering and kept warm for 3 hours to obtain a curved magnesium-aluminum spinel transparent fairing.
[0042] The transmittance of the magnesium-aluminum spinel transparent fairing in Example 1 was tested by an ultraviolet-visible-near infrared spectrophotometer. Before the test, the magnesium-aluminum spinel transparent fairing in Example 1 was double-sided mirror polished, and the wavelength range of the test was 3-5 μm. The Vickers hardness and fracture toughness (indentation method) of the magnesium-aluminum spinel transparent ceramic fairing were tested by a Vickers hardness tester.
[0043] The curved magnesium aluminum spinel transparent fairing prepared in Example 1 has a transmittance of ≥85%@3-5μm, a hardness of ≥14.2GPa, and a fracture toughness of ≥2.3MPa.m 1 / 2 .
[0044] Embodiment 2:
[0045] A method for preparing a curved magnesium-aluminum spinel transparent fairing comprises the following steps: Step 1: Mix 99.92% pure magnesium aluminum spinel powder, 4.127 g lithium fluoride and 1445 mL deionized water, ball mill at 50 rpm for 24 h, dry at 105 ° C for 28 h, and pass through a 40-mesh sieve to obtain a modified powder; Step 2, adding 60wt% of the modified powder into a hot pressing mold, placing a curved molybdenum paper above the modified powder, so that the concave surface of the curved molybdenum paper faces upward and the convex surface is embedded in the modified powder, and adding the remaining modified powder to fill the concave surface of the curved molybdenum paper to obtain a sintered precursor; Step 3, heating the sintered precursor to 800°C at a heating rate of 5°C / min, and keeping it warm for 90 minutes to obtain a pretreated sintered product; in an inert atmosphere, heating the pretreated sintered product to 1150°C at a heating rate of 4°C / min for a second time, and keeping it warm for 10 minutes to obtain a secondary sintered product; under a pressure of 35MPa, heating the secondary sintered product to 1550°C at a heating rate of 4°C / min for three times, keeping it warm for 5 hours for three times, naturally cooling to 1500°C, releasing the pressure, and naturally cooling to room temperature to obtain a hot pressed sample; Step 4: Take the hot-pressed sample out of the hot-pressing mold, separate the sample along the molybdenum paper, and the lower half is the curved surface sample blank, which is processed and polished according to size requirements to obtain a rough fairing; Step 5: In an inert atmosphere at 160 MPa, the crude fairing product is heated to 1750° C. for sintering and kept warm for 3 hours to obtain a curved magnesium-aluminum spinel transparent fairing.
[0046] The transmittance of the magnesium-aluminum spinel transparent fairing in Example 2 was tested by an ultraviolet-visible-near infrared spectrophotometer. Before the test, the magnesium-aluminum spinel transparent fairing in Example 2 was double-sided mirror polished, and the wavelength range of the test was 3-5 μm. The Vickers hardness and fracture toughness (indentation method) of the magnesium-aluminum spinel transparent ceramic fairing were tested by a Vickers hardness tester.
[0047] The curved magnesium aluminum spinel transparent fairing prepared in Example 2 has a transmittance of ≥85%@3-5μm, a hardness of ≥14GPa, and a fracture toughness of ≥2.3MPa.m 1 / 2 .
[0048] Embodiment 3:
[0049] A method for preparing a curved magnesium-aluminum spinel transparent fairing comprises the following steps: Step 1: Mix 99.95% pure magnesium aluminum spinel powder, 2.519 g lithium fluoride and 882 mL deionized water, ball mill at a speed of 50 rpm for 24 h, dry at a temperature of 105 ° C for 28 h, and pass through a 40-mesh sieve to obtain a modified powder; Step 2, adding 80wt% of the modified powder into a hot pressing mold, placing a curved molybdenum paper above the modified powder, so that the concave surface of the curved molybdenum paper faces upward and the convex surface is embedded in the modified powder, and adding the remaining modified powder to fill the concave surface of the curved molybdenum paper to obtain a sintered precursor; Step 3, heating the sintered precursor to 800°C at a heating rate of 5°C / min, and keeping it warm for 75 minutes to obtain a pretreated sintered product; in an inert atmosphere, heating the pretreated sintered product to 1150°C at a heating rate of 4°C / min for a second time, and keeping it warm for 10 minutes to obtain a secondary sintered product; under a pressure of 35MPa, heating the secondary sintered product to 1550°C at a heating rate of 4°C / min for three times, keeping it warm for 5 hours for three times, naturally cooling to 1500°C, releasing the pressure, and naturally cooling to room temperature to obtain a hot pressed sample; Step 4: Take the hot-pressed sample out of the hot-pressing mold, separate the sample along the molybdenum paper, and the lower half is the curved surface sample blank, which is processed and polished according to size requirements to obtain a rough fairing; Step 5: In an inert atmosphere and at 160 MPa, the crude fairing product is heated to 1700° C., sintered, and kept warm for 3 hours to obtain a curved magnesium-aluminum spinel transparent fairing.
[0050] The transmittance of the magnesium-aluminum spinel transparent fairing in Example 3 was tested by an ultraviolet-visible-near infrared spectrophotometer. Before the test, the magnesium-aluminum spinel transparent fairing in Example 3 was double-sided mirror polished, and the wavelength range of the test was 3-5 μm. The Vickers hardness and fracture toughness (indentation method) of the magnesium-aluminum spinel transparent ceramic fairing were tested by a Vickers hardness tester.
[0051] The curved magnesium aluminum spinel transparent fairing prepared in Example 3 has a transmittance of ≥85%@3-5μm, a hardness of ≥14GPa, and a fracture toughness of ≥2.3MPa.m 1 / 2 .
[0052] Comparative Example 1:
[0053] A conventional method for preparing a curved magnesium-aluminum spinel transparent fairing specifically comprises the following steps: Step 1: Evenly mix the magnesium aluminum spinel powder, anhydrous ethanol and sintering aid in a ball mill for two hours, wherein the volume ratio of magnesium aluminum spinel powder to anhydrous ethanol is 1:9, and the content of sintering aid is 0.05wt%. The prepared magnesium aluminum spinel slurry is dried and sieved to obtain a uniformly mixed powder raw material. Step 2: dry-press the uniformly mixed powder raw materials at a pressure of 20 MPa for 3 min to obtain a ceramic blank; Step 3: Place the obtained green body in a muffle furnace for pre-sintering, raise the temperature to 600°C, and keep the temperature for 2-6 hours to obtain a pre-sintered body; Step 4: The pre-sintered body is pressurelessly sintered in an air atmosphere, heated to 1100°C at a heating rate of 5°C / min, kept warm for 1 hour, and further heated to 1300°C at a heating rate of 3°C / min, kept warm for 10 hours, and cooled to room temperature with the furnace to obtain a magnesia-alumina spinel sample. Step 5: Place the magnesium-aluminum spinel sample in a hot isostatic pressing furnace with a hot pressing pressure of 150 MPa. In an argon atmosphere, the temperature is raised to 1600° C. and kept at this temperature for 1 hour. Step 6: The hot isostatically pressed sample is subjected to coarse grinding, fine grinding and polishing to obtain a curved magnesium-aluminum spinel transparent fairing.
[0054] The transmittance of the magnesium-aluminum spinel transparent fairing in Comparative Example 1 was tested by using an ultraviolet-visible-near-infrared spectrophotometer. Before the test, the magnesium-aluminum spinel transparent fairing in Comparative Example 1 was double-sided mirror polished, and the wavelength range of the test was 3-5 μm. The Vickers hardness and fracture toughness (indentation method) of the magnesium-aluminum spinel transparent ceramic fairing were tested by using a Vickers hardness tester.
[0055] The curved magnesium aluminum spinel transparent fairing prepared in Comparative Example 1 has a transmittance of <70%@3-5μm, a hardness of <12GPa, and a fracture toughness of <1.9MPa.m 1 / 2
[0056] By comparing the transmittance, hardness and fracture toughness of the curved magnesium aluminum spinel transparent fairing prepared in Examples 1-3 and Comparative Example 1, it can be seen that the curved magnesium aluminum spinel prepared in Examples 1-3 of the present invention has good transmittance, hardness and fracture toughness. This is because the present invention uses curved molybdenum paper to shape the sample in combination with hot pressing and sintering treatment to make the modified powder evenly stressed during the hot pressing process, promote the densification of the fairing, reduce pores and grain boundary scattering, and improve transparency and mechanical properties. At the same time, the present invention uses a staged heating method to obtain a better phase structure and microstructure. In addition, the present invention also uses hot isostatic pressing technology to further improve the optical quality and mechanical strength of the curved magnesium aluminum spinel transparent fairing.
[0057] In summary, the preparation method of the curved magnesium-aluminum spinel transparent fairing provided by the present invention can effectively improve the transmittance, hardness and fracture toughness of the curved magnesium-aluminum spinel transparent fairing.
[0058] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modification, equivalent substitution or improvement made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a curved magnesium aluminum spinel transparent fairing, characterized in that: The steps include: Step 1: Evenly mix the magnesium aluminum spinel powder, sintering aid and deionized water, ball mill, dry and sieve to obtain modified powder; Step 2: adding part of the modified powder into a hot pressing mold, placing a high temperature resistant curved mold above the modified powder, with the concave surface of the high temperature resistant curved mold facing upward and the convex surface embedded in the modified powder, and adding the remaining modified powder to fill the concave surface of the high temperature resistant curved mold to obtain a sintered precursor; Step 3, heating the sintering precursor to 750° C.-850° C. and keeping the temperature to obtain a pre-treated sintered product; In an inert atmosphere, the pretreated sintered product is heated to 1140° C.-1160° C. for a second time, and kept warm for a second time to obtain a secondary sintered product; under a pressure of 30 MPa-40 MPa, the secondary sintered product is heated to 1500° C.-1600° C. for a third time, and kept warm for a third time to obtain a hot pressed sample; Step 4, separating the hot pressed sample from the mold, processing and polishing, and obtaining a rough fairing product; Step 5: In an inert atmosphere at 150 MPa-170 MPa, the crude fairing product is heated to 1650° C.-1750° C. and sintered to obtain a curved magnesium-aluminum spinel transparent fairing.
2. The method for preparing the curved magnesium aluminum spinel transparent fairing according to claim 1, characterized in that: In step 1, the sintering aid is lithium fluoride; and / or In step 1, the purity of the magnesia-alumina spinel powder is ≥ 99.9%.
3. The method for preparing the curved magnesium aluminum spinel transparent fairing according to claim 1, characterized in that: In step 1, the amount of the sintering aid added is 1wt%-1.5wt% of the magnesia-alumina spinel powder; and / or In step 1, the mass volume ratio of the magnesia alumina spinel powder to the deionized water is 1g:(3mL-4mL).
4. The method for preparing the curved magnesium aluminum spinel transparent fairing according to claim 1, characterized in that: In step 1, the ball milling speed is 50 rpm-60 rpm; the ball milling time is 24h-26h; and / or In step 1, the mesh size of the sieving is 10-80 mesh.
5. The method for preparing the curved magnesium aluminum spinel transparent fairing according to claim 1, characterized in that: In step 2, the portion of the modified powder is 60%-80% of the total volume of the modified powder; and / or In step 2, the high temperature resistant curved mold is curved molybdenum paper.
6. The method for preparing the curved magnesium aluminum spinel transparent fairing according to claim 1, characterized in that: In step three, the first, second and third heating are all performed by programmed heating; wherein the heating rate of the first heating is 4°C / min-6°C / min; the heating rates of the second and third heating are all 3°C / min-4°C / min.
7. The method for preparing the curved magnesium aluminum spinel transparent fairing according to claim 1 or 6, characterized in that: In step 3, the time of the first insulation is 60min-90min; and / or In step 3, the secondary insulation time is 9 min-12 min; and / or In step 3, the three insulation times are 4h-6h.
8. The method for preparing the curved magnesium-aluminum spinel transparent fairing according to claim 1, characterized in that: In step 5, the sintering holding time is 2h-4h; and / or In step five, the heating rate of the fairing crude product is 3°C / min-7°C / min.
9. A curved magnesium aluminum spinel transparent fairing, characterized in that: The curved magnesium-aluminum spinel transparent fairing is prepared by the preparation method of any one of claims 1 to 8.
10. Application of the curved magnesium aluminum spinel transparent fairing as claimed in claim 9 in an infrared optoelectronic imaging guidance system.